VSIG4 as a tumor-associated macrophage marker predicting adverse prognosis in diffuse large B-cell lymphoma - Ma, Dongshen; Wang, Yubo; Shen, Qingqing; Liu, Xinyu; Lu, Wenxin; Li, Shaoqi; Yin, Qianqian; Xia, Lei; Liu, Guangzhen; Chen, Yuhong; Xiang, Chenxi; Liu, Hui (Frontiers in Immunology, 2025)
IntroductionDiffuse large B-cell lymphoma (DLBCL) exhibits heterogeneous tumor microenvironment. However, the role of tumor-associated macrophages (TAMs) in the DLBCL tumor microenvironment remains unclear. This study aims to elucidate the heterogeneity of TAMs in DLBCL to identify critical TAM-associated prognostic biomarkers.MethodsTranscriptome data from DLBCL patients were obtained from online database. The CIBERSORT algorithm was applied to quantify TAM abundance across samples. Consensus clustering was used to stratify DLBCL into distinct clusters based on TAM subtype enrichment. Differential gene expression analysis, LASSO regression, univariate/multivariate Cox regression and Kaplan-Meier survival analysis were employed to identify key prognostic biomarkers. Validation of VSIG4+TAM subpopulation was performed using flow cytometry and multiplex immunohistochemistry. A local cohort of 375 DLBCL patients was investigated to explore the correlation between VSIG4 expression and various genetic and pathological characteristics including prognostic outcomes.ResultsFour distinct DLBCL clusters, each enriched with specific TAM subtypes were found. The cluster dominated by M2 TAMs exhibited the worst prognosis. Differential analysis identified VSIG4 as a critical prognostic factor, with high expression in the M2 TAM-enriched cluster. Flow cytometry and mIHC confirmed VSIG4+ TAMs as a subpopulation within CD68+/CD163+ M2 macrophages. VSIG4 expression correlated with adverse genetic features (PIM1, ETV6, CD70 mutations) and aggressive pathological characteristics (non-GCB phenotype, MYC+/BCL-2 double-expression). Multivariate Cox regression confirmed VSIG4 as an independent prognostic factor for poor survival. Survival analysis suggested that VSIG4’s prognostic impact operates independently of regulating lymphocyte infiltration, highlighting its unique role in DLBCL tumor microenvironment. DiscussionThis study identifies VSIG4 as a TAM-associated marker of adverse prognosis of DLBCL and the expression of VSIG4 is related to high-risk genetic and pathological features. These findings position VSIG4 as a promising therapeutic target for immune checkpoint intervention in DLBCL.